Tamed stability and transport using controlled non-axisymmetric fields in KSTAR. (22nd March 2019) - In, Yongkyoon; Jeon, Y.M.; Park, J.-K.; Loarte, A.; Ahn, J.-W.; Lee, J.H.; Lee, H.H.; Park, G.Y.; Kim, K.; Kim, H.S.; Ko, W.H.; Rhee, T.; et al.
Abstract: Meticulously orchestrated non-axisymmetric fields ( δB ) enabled KSTAR to explore various paths to tame plasma stability and transport in a very rigorous manner. Given an extremely low level of intrinsic non-axisymmetry, KSTAR has now established high-precision 3D field control capability that can not only robustly suppress edge localized modes (ELM) using resonant magnetic perturbation (RMP), but also exclusively alter plasma rotation without invoking particle and energy transport. In highly shaped plasmas (triangularity of δ 0.6), we have secured low- n RMP-driven, ELM-crash suppressions in a wide range of edge safety factor at q 95 = 3.4–6.4. One of the best n = 1 RMP-driven, ELM-crash suppressions has been sustained for more than 30 s (comparable to wall saturation time), satisfying a low edge collisionality ( ν * 0.2) at Z eff = 1, close to ITER-target. Besides a routinely used three-row RMP configuration, we have newly succeeded in suppressing ELM-crashes using n = 1 off-midplane RMPs only, whose helical structure in vacuum appears nearly orthogonal to a typical configuration. Nonetheless, when the plasma response is factored, the off-midplane RMP configuration remains dominantly resonant. With RMP configuration fixed, a gradual torque control between 'perpendicular' and tangential components of neutral beams probed the onset of ELM-crash-suppression, strongly endorsing the existence of ω ⊥, e 0 at pedestal top as necessary condition for ELM-crash-suppression, consistent with direct measurement of ECEI. In support of ITER, KSTAR has demonstrated broadened divertor heat fluxes during ELM-crash-suppression, as well as during ELM-crash-mitigation, using intentionally misaligned RMP configurations. However, we have found that such a misaligned configuration, as had effectively broadened the divertor heat fluxes during ELM-crash-mitigation, did not show a similar broadening during ELM-crash-suppression. This suggests that the divertor heat flux during ELM-crash-suppression, governed by a bifurcated state of δB, may not be appropriately projected, based on the results of ELM-crash-mitigation, in which the linear plasma response of δB prevails.